Students’ Mathematical Communication Skills Based on Keirseys’ Personality Types of Idealist and Gender - Mulyastuti, Indah Dwi; Budiyono, Budiyono; Indriati, Diari (Journal of Mathematics and Mathematics Education, 2019)
Learning in the 21st century can be defined as learning that provides 21st century skills, one of which is communication. Mathematics learning allows students to communicate mathematical ideas clearly. Different personality types can affect the way they communicate, and other activities in learning mathematics. This study aims to describe students' mathematical communication skills in terms of Keirsey personality types, namely Idealist and gender who have Idealist personalities. Descriptive qualitative research was used in this research and was carried out at Junior High School Negeri 1 Purwodadi in the 2019/2020 school year. The research was conducted on the subject of class VIII I with idealist personality type, then selected 1 female student and 1 male student using purposive sampling. The researcher is the main research instrument with the help of observation guidelines, questionnaires, tests of mathematical communication skills and then interviews. The data collection technique is a triangulation technique by comparing the answers to the mathematical communication skills test and interviews. Data reduction, data presentation and drawing conclusions are data analysis techniques used in this study. Female students with idealist personality types communicate better mathematically than male students with idealist personality types as shown in the results of this study.